دراسة تأثير بعض وسائط الفرملة على تخفيض سرعة السفينة خلال المرحلة الرابعة من مراحل الإنزال الطولي للسفن إلى الماء - ميشيل بربهان; إيهاب صالح (Tishreen University, 2014)
يُعَدُّ الإنزال الطولي للسفن من أهم طرق الإنزال إلى الماء بعد الانتهاء من البناء أو القيام بعمليات  الإصلاح والصيانة. وهذه الطريقة من الإنزال خطيرة جداً، ولا يمكن التحكم بها بعد بدء عملية الإنزال؛ لأنها تمثل انتقالاً تلقائياً لكتلة كبيرة جداً. لهذا السبب ينبغي التحضير لهذه العملية بعناية فائقة مع أخذ أدق التفاصيل الممكنة بالحسبان. فعندما تبدأ السفينة بالحركة (بالانزلاق) يصبح العنصر البشري مراقباً عديم التأثير في مسار آلية الإنزال. ومن هنا تأتي أهمية إنجاز الحسابات بدقة عالية لضمان إنزال السفينة بشكل آمن الى الماء, والسفينة في أثناء الإنزال تغادر المزلق المائل عادة بسرعة كبيرة, فإذا كان عرض الحوض المائي غير كاف, تكون السفينة عرضة للاصطدام بالرصيف المقابل لهذا الحوض ولتجنب حدوث ذلك تستخدم وسائط خاصة تهدف إلى إنقاص سرعة السفينة أثناء إنزالها. يتناول هذا البحث دراسة فرملة حركة السفينة بطريقتي الصفائح والجنازير وباستخدام الطريقتين كليهما معاً كوسيلة فرملة واحدة خلال المرحلة الرابعة من عملية الإنزال الطولي بعد مغادرتها المزلق المائل. لقد أظهرت النتائج فعالية كبيرة لطريقة الفرملة بالجنازير بالمقارنة مع طريقة الفرملة بالصفائح.   The longitudinal launching  of ships is the most important ways for landing to the water after completion of construction or doing repair and maintenance processes. This way of launching  is very dangerous, and can not be controlled after the start of the process of landing, because it represents the transition automatically a very large mass. For this reason they should be preparing for this process very carefully, taking into account the smallest details possible. When the ship starts moving (sliding),the human factor become an observer and useless on influence the course of launching mechanism. Hence, the importance of accurate calculation came to ensure the launching ship into the water in safe way. The ship usually leaves the leaning slip with high velocity during the launching. If the width of the dock isn't enough, the ship is subjected to clash with the pavement that is opposite to the dock. So, to avoid this, we usually use special modes that purpose to reduce the speed of the ship during launching. This research discuss studying braking the movement of the ship using the plates and chains and also when used together as a single braking way during the fourth stage of launching process after it leaves the leaning slip. The results showed significant efficacy in a method braking by chains compared with method braking by plates.